2009
DOI: 10.1038/eye.2009.149
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid and protein contents of lens proteolipids in human senile cataract

Abstract: Purpose This experimental study was conducted with the aim of evaluating the quantitative change, if any, in the phospholipids and protein contents of lens proteolipids during cataract formation, and to establish whether the phospholipid/protein content of the blood is related to cataractogenesis. Methods A total of 120 human lenses were collected. Phospholipids and protein content in proteolipids of these lenses were estimated biochemically. Blood was examined from total 60 persons. Data obtained were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It can be opposed that the absence of marked changes is due to insufficiency to visualize small objects alongside the omnipresent protein spectrum that dominates the Raman spectrum. In the lens the overall phospholipid and cholesterol content is less than 5% of dry weight (Li et al, 1985;Siddique et al, 2010). The small red and orange regions in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…It can be opposed that the absence of marked changes is due to insufficiency to visualize small objects alongside the omnipresent protein spectrum that dominates the Raman spectrum. In the lens the overall phospholipid and cholesterol content is less than 5% of dry weight (Li et al, 1985;Siddique et al, 2010). The small red and orange regions in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…[ 18 ] The perfect physicochemical arrangement of the lens proteins gives transparency to the lens. [ 19 ] Protein aggregation increases with age. The crystallins, which constitute approximately 90% of the TPC of the lens, accumulate, and show many age-related oxidative changes.…”
Section: Discussionmentioning
confidence: 99%
“…The major fatty acids were C160, C24:l and C24:0, and monounsaturated fatty acids accounted for 40-55% the total fatty acids [74]. Siddique et al reported alterations of phospholipid and protein moieties in lens fibers, disrupting function and leading to cataract formation (Figure 3) [75].…”
Section: Lipid and Cataractsmentioning
confidence: 99%